Simbolicità e emotività negli animali non umani: un tema attuale con radici lontane - Gensini, Stefano; Palazzolo, Giulia (Rivista Italiana di Filosofia del Linguaggio, 2020)
Are the communication systems of non-human animals endowed with the property of symbolism or are they merely expressions of emotional states? The question has pervaded the philosophical debate at least since the time of Descartes and is now abundantly discussed in the field of cognitive ethology. In this paper, the topic is summarized both from the philosophical point of view (reconsidering Brentan’s notion of ‘intentionality’, often referred to by ethologists, too) and from the experimental point of view, referring to some well-known case-studies of the last decades. It is suggested that a dichotomous, all-or-nothing, vision of the relationship between symbolism and emotionality is, today, outdated in both conceptual and methodological terms. Available evidence on the communication of different primate species shows that the two components interact closely. An embodied approach to animal communication seems to represent an effective way out also from a theoretical point of view.